Local sediment amendment can potentially increase barley yield and reduce the need for phosphorus fertilizer on acidic soils in Kenya - Scherwietes, Eric; Stein, Mathias; Six, Johan; Bawen, Titus Kiplagat; Schaller, Jörg (Frontiers in Environmental Science, 2024)
Soil acidification and low nutrient availability are two major challenges facing agriculture in most regions of East Africa, resulting in aluminum toxicity and poor crop yields. The amendment of local sediments to cropland can potentially alleviate these challenges, but responses are variable. In this study, we investigated the potential of two different local sediments influenced by volcanic deposits to increase soil pH, Si and P availability and reduce Al toxicity, thereby improve barley yield. Hence, a field experiment was established in Eldoret, Western Kenya, using 1 % and 3 % addition by weight of two sediments in barley cultivated plots. The Baringo 3 % amendment significantly increased soil pH (from 4.7 to 7.0), the available P content (from 0.01 mg g -1 to 0.02 mg g -1 ) and decreased the Al availability (from 3.03 mg g -1 to 2.17 mg g -1 ). This resulted in a barley yield of 4.7 t/ha (+1061 %). The Nakuru 3 % and Baringo 1 % amendments increased yield to 2-3 t/ha, while the Nakuru 1 % did not significantly increase yield. These results highlight that, from a biophysical perspective, there are natural and local opportunities to reduce soil acidification and to partly replace mineral fertilizer, but its magnitude depends on the sediment and the amendment rate.